Fish Behavior as a Neural Proxy to Reveal Physiological States - Fu, Chih-Wei; Horng, Jiun-Lin; Chou, Ming-Yi (Frontiers in Physiology, 2022)
Behaviors are the integrative outcomes of the nervous system, which senses and responds to the internal physiological status and external stimuli. Teleosts are aquatic organisms which are more easily affected by the surrounding environment compared to terrestrial animals. To date, behavioral tests have been widely used to assess potential environmental risks using fish as model animals. In this review, we summarize recent studies regarding the effects of internal and external stimuli on fish behaviors. We concluded that behaviors reflect environmental and physiological changes, which have possible implications for environmental and physiological assessments.